THE SOCIAL VALUES OF MANGAN MERANGKAT'S EVENT IN THE SASAK TRADITIONAL MARRIAGE IN PERINA VILLAGE: TO THE DIRECTION OF STRENGTHENING OF SOCIOLOGY TEACHING SUPPLEMENTSIOLOGY TEACHING SUPPLEMENTS - Astiti listia Utari; Masyhuri Masyhuri; Sukardi Sukardi (Jurnal Pendidikan Sosial Keberagaman, 2020)
AbstracThis research was conducted to examine the process of the mangan merangkat's event and the forms of social values that contained in the mangan merangkat's event at the traditional marriage of the Sasaknese in Perina Village. This study aims to 1) find out the process in the mangan merangkat's event in Perina Village, 2) find out the forms of social values that contained in the mangan merangkat's event at the Sasak traditional marriage in Perina Village. This research uses a qualitative approach with ethnographic methods. The data collection techniques in this study using interviews, observation, and documentation. The results of this study found that 1) the process of the mangan merangkat's event in Perina Village started from a) preparation, b) cooking, and c) eating together or begibung. 2) the forms of social values in the mangan metangkat's event took place in the Sasak traditional marriage in Perina Village, namely: 1) help, 2) kinship, 3) caring, 4) empathy, and 5) cooperation.